2015
DOI: 10.1177/000313481508100307
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Tumor: Mucinous Cystadenocarcinoma of the Breast

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.In general, authors of case reports should use the Brief Report format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…All the cases reported to date conform to the original morphological description by Koenig and Tavassoli 1 with only minor variations. 2-19 Similar to their original description, all cases of MCA exhibited abundant intracellular mucin along with extracellular mucin in the center of cystically dilated ducts. However, extravasation of mucin in the adjacent stroma was not a constant feature, being present in only 10 cases including ours.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…All the cases reported to date conform to the original morphological description by Koenig and Tavassoli 1 with only minor variations. 2-19 Similar to their original description, all cases of MCA exhibited abundant intracellular mucin along with extracellular mucin in the center of cystically dilated ducts. However, extravasation of mucin in the adjacent stroma was not a constant feature, being present in only 10 cases including ours.…”
Section: Discussionsupporting
confidence: 63%
“…Since its first description by Koenig and Tavassoli in the year 1998, only 23 cases of MCA of breast have been reported in the literature. 1-19 Most consist of sporadic case reports describing the histopathological and IHC features. Because of the rarity of the tumor, the histogenesis and biological behavior of this neoplasm is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…MCA of the breast is an extremely rare tumor. It is homologous to MCA of the ovary and pancreas [ 10 ]. MCA has distinct pathologic features compared with mucinous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of ordinary DCIS and MCA in 6 of 21 cases, indicates that tumour cells of MCA might have been transformed from epithelial cells of ordinary DCIS via a process of metaplasia, accompanied by loss of expression of estrogen receptor and progesterone receptor. 3,5,6,18,19 In two cases, both mucinpositive and mucin-negative tumour cells were found in the coexisting ordinary DCIS adjacent to the MCA. In some cases, this certain histological type of breast cancer seems to originate from the main mammary duct, next to the nipple, but the CCMC in the present case was quite far from the nipple.…”
Section: Discussionmentioning
confidence: 95%
“…3 A review of the literature revealed only 21 reports of this histological type. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The carcinoma of this certain histological type is possible to appear to the naked eye either cystic, being characterised as MCA or solid, being characterised as CCMC. 1 Of the 21 cases, only 3 until now have been reported to belong to the solid columnar cell type and our case is one of them.…”
Section: Discussionmentioning
confidence: 99%